2001
DOI: 10.1086/323810
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Invasive Capacity of Quinolone‐ResistantEscherichia coliin Patients with Urinary Tract Infections

Abstract: Quinolone-resistant (QR) Escherichia coli may have lower invasive capacity than does quinolone-susceptible E. coli. To evaluate this, we prospectively collected data regarding all cases of E. coli invasive urinary tract infections (IUTI) in 669 adults admitted to the Infectious Diseases Unit of our hospital during a 3-year period, as well as 10,950 patients with cystitis or asymptomatic bacteriuria who presented to the outpatient clinic during a 1-year period. QR E. coli was isolated in 20% of patients with cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
50
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 14 publications
6
50
2
Order By: Relevance
“…Although some investigators suggested that virulence genes increased antibiotic resistance of previously resistant strains (16), others observed that quinoloneresistant E. coli strains were more prone to induce Cys rather than PN (17,18,20) because of decreased renal invasive capacity concomitantly acquired by the mutation. Our findings, in agreement with those reports, showed a lower proportion of E. coli resistance to first-generation quinolones in PN isolates: the risk of resistance in PN isolates to nalidixic acid was reduced in the whole sample (OR ϭ 2.90) and to pipemidic acid in the Tx group (OR ϭ 2.57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some investigators suggested that virulence genes increased antibiotic resistance of previously resistant strains (16), others observed that quinoloneresistant E. coli strains were more prone to induce Cys rather than PN (17,18,20) because of decreased renal invasive capacity concomitantly acquired by the mutation. Our findings, in agreement with those reports, showed a lower proportion of E. coli resistance to first-generation quinolones in PN isolates: the risk of resistance in PN isolates to nalidixic acid was reduced in the whole sample (OR ϭ 2.90) and to pipemidic acid in the Tx group (OR ϭ 2.57).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, other investigators have suggested that quinolone resistance involves a genotypic change associated with the loss of virulence factors in E. coli (17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Recent data suggests that quinolone resistance could be directly associated with loss of virulence, that is, quinolone-resistant E. coli strains express fewer virulence factors than quinolone-susceptible strains [3,7,8]. It has been generally assumed that bacteria pay a physiological price -fitness deficit-for their acquisition of resistance to antibiotics [11].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, mechanisms of quinolone action and resistance have been thoroughly studied and discussed by many authors [4][5][6]. Acquisition of quinolone resistance has been commonly associated with reduced fitness and decreased virulence of E. coli strains [7,8]. Thus, the mechanisms by which quinoloneresistant E. coli strains compensate for this loss of fitness are of special importance for understanding the factors essential for their survival and persistence.…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis seems very attractive and, indeed, there are many reports indicating that highly resistant urinary E. coli strains are not usually involved in invasive disease. 12,13 However, although the molecular basis of quinolone resistance in E. coli is fairly well known, 14,15 there is no established genetic relationship between quinolone resistance and virulence factors. Another mechanism proposed to explain the low incidence of quinolone-resistant E. coli SBP is that norfloxacin might inhibit bacterial translocation, an event that precedes SBP.…”
Section: Discussionmentioning
confidence: 99%